Psychological Health Factors in Young and Elderly People - T.N. Reznikova; I.V. Chikhachev; S.E. Abbasova; N.A. Seliverstova (Клиническая и специальная психология)
The article examines the problem of preserving and maintaining human health from the standpoint of the biopsychosocial approach, the theory of functional systems by P.K. Anokhin, the theory of development and functioning of higher mental functions, as well as the concept of cerebral information fields and the psychological information fields of the brain formed on their basis. The empirical part of the article focuses on studying of psychological factors affecting the health of young and elderly people with mild cognitive impairment (MCI) in a calm and post-stress state. The study reveals the features of the negative impact of stress on psychological health in young and elderly people with MCI, as well as highlights the factors contributing to the deterioration or maintenance of psychological health in different age groups. It was found that in a stressful situation, elderly people with MCI have a more differentiated reaction to stress compared to young people, and indicators of self-esteem and cognitive functions remain at the same level, while young people in a stressful situation demonstrate an undifferentiated reaction leading to personal maladaptation, deterioration of cognitive functions and greater severity of negative emotions (anxiety, fear, aggression, depression). The data obtained indicate a greater ability of elderly people with MCI to regulate their psychological health, compared with younger people, due to the formed positive stable attitude towards maintaining health.